Coumarin-Phosphazenes: Enhanced Photophysical Properties from Hybrid Materials - Sahin, Mehmet Emrah; Biryan, Fatih; Caliskan, Eray; Koran, Kenan (Amer Chemical Soc, 2024)
Phosphazenes have drawn a great deal of interest over the past 20 years as a potentially useful building block for the fabrication of fluorescent materials. The main objective of this work is to explore novel derivatives produced by coumarins, a class of chemicals well-known for their photophysical importance, and cyclophosphazenes. UV absorbance, fluorescence emission, quantum yield, and lifetime measurements were conducted to comprehend the optical properties. Furthermore, single-crystal X-ray analysis and theoretical calculations were carried out to confirm the structure of the molecule. The obtained findings collectively confirm the commendable optical properties exhibited by the studied compounds. Moreover, a detailed study of the crystal packing arrangement of DPP-Et-Kum-Et compound crystallized in the P2(1)/n monoclinic space group revealed the presence of stacking interactions between the nonplanar conjugated benzene rings of the coumarins and the rigid diphenyl groups attached to the phosphazene ring. The crystal structure of the DPP-Kum-Me-Me compound is mainly based on classical C-HO intermolecular hydrogen bonding interactions with an average distance of 2.52 & Aring;. Importantly, the calculated absorption spectra of the compounds are in close agreement with the experimental data, further supporting their interesting electronic properties. Given that the DPP-Et-Kum-Et and DPP-Kum-Et compounds have the theoretically lowest band gaps (4.31 and 4.30 eV, respectively), the activation energies of these compounds were determined by an impedance analyzer using dc conductance values measured at different temperatures. The calculated activation energies for DPP-Et-Kum-Et and DPP-Kum-Et are 104.49 and 100.92 meV, respectively. The results demonstrate that both theoretical and experimental calculations are in agreement with each other and that the DPP-Kum-Et compound has the lowest conductivity.
Keywords: Zinc-Oxide Nanoparticles; Fluorescence; Conductivity; Derivatives; Design; Polyphosphazenes; Exchange